The effects of organic selenium supplementation on the rumen ciliate population in sheep - Mihaliková, K; Gresáková, L; Boldizárová, K; Faix, S; Leng, L; Kisidayová, S (Folia microbiologica, 2005)
The effect of selenium supplementation on the rumen protozoan population of sheep was demonstrated. Both the total and generic counts of rumen ciliates in sheep fed a diet with basal Se content (70 microg/kg dry matter) were compared to those of animals given feed supplemented with inorganic (disodium selenite) or organic Se (selenized yeast) (310 microg/kg dry matter). The genera of Entodinium, Isotricha, Dasytricha, Ophryoscolex, Diploplastron and Polyplastron occurred in all sheep except for the control, in which Ophryoscolex was not observed. The population of Ophryoscolex caudatus f. tricoronatus was significantly higher in sheep supplemented with organic Se than in animals given inorganic Se (by 160 %). Supplementation of feed with selenized yeast induced significant growth in the Diploplastron population (by 63 %) while no change occurred in sheep given selenite. The populations of Dasytricha ruminantium and Polyplastron multivesiculatum were higher than control in both Se-supplemented groups. The ciliate population of Entodinium spp. was not influenced by Se supplements. Our results suggest a protective effect of Se feed supplementation on the development of some rumen ciliate species in young ruminants.
Keywords: Organic Chemicals; anorganické látky; Animals; Dietary Supplements; organické látky; Inorganic Chemicals; Rumen; zvířata; selen; Sheep, Domestic; Ciliophora; bachor; potravní doplňky; Selenium; ovce domácí